A study on the role of customer experience and consumer purchase decision in Luxury Fashion. - Patanwala, Taher (2022)
The particular topic of factors influencing consumer purchase decision and customer experience in luxury fashion was chosen as experience is one of the most up coming factors for specially luxury industry. The topic is covered under six different chapters to give an in depth understanding of the significance of customer experience, sustainability, and luxury fashion. The literature used to justify the subject is from scholarly journals. There are many concepts covered under this subject like greenwashing, circular economy, experience economy, and sustainable fashion and so on. The research method chosen was a qualitative approach wherein the in depth interview method with selective coding and thematic analysis were applied to analyse the research. A data structure is been prepared after the data collection and analysis in order to sum up the lumpsum amount of data collected from the interviews and to understand the differences and similarities the research has from the literature applied. The direct quotes have also been used as way to show evidence of the research conducted. Lastly the conclusion includes a brief summary of the findings and literature with further limitations and directions for future research.